Dual-mode porous and highly graphitized 3D nitrogen-doped carbon network as an advance anode material for sodium-ion batteries - Dar, Mudasir; Suresh, Karthika; Majid, Kowsar; Wahid, Malik (Journal of Physical Chemistry C, 2023)
The practical application of hard carbons as the mostappealinganode material for sodium-ion batteries is hampered by their poorcycling and rate performances, emanating from poor electrochemicalstability, low electroconductivity, and sluggish Na+ transport.Designing a single remedial method for these challenges often involvescomplex and energy-intensive processes, contradicting the core conceptof cost-effectiveness for practical energy storage technology. Herein,we employed trifunctional silica (SiO2): as colloidal silicato ice template micron-sized pores, as a hard template for nanopores,and as a catalyst for the graphitization of carbon for the synthesisof a highly graphitized, efficiently nitrogen-doped, high-surface-area,three-dimensional porous carbon network (3D PNC) with dual-mode porosity(nanopores and micron-sized pores). As an anode material, the obtained3D PNC exhibits a reversible capacity of 262 mAh g(-1) at a current density of 100 mA g(-1), an ultrahighrate capability of 173 mAh g(-1) at 1 A g(-1), and a stable cycling life of 1000 cycles at a high current densityof 100 mA g(-1) with almost 100% capacity retention.The galvanostatic intermittent titration technique (GITT) revealsfacile sodium diffusion kinetics with an average diffusion coefficientof an order of & SIM;10(-9) (cm(2) s(-1)), which is fairly low compared to most reported HCanodes for SIBs. This work demonstrates how a merger of two or moresynthesis methodologies can be employed for the advanced microstructureengineering of carbon materials, opening up new avenues for the rationaldesign of anode materials in SIBs.